PENGARUH UKURAN PERUSAHAAN, NET PROFIT MARGIN DAN DEBT TO EQUITY RATIO TERHADAP AUDIT DELAY (Jurnal Akuntansi, 2020)
The purpose of this research is is to test the influence the size of  company, net profit margins and debt to equity ratio about the audit delay. The population in this research is the sub-sector companies listed on the Indonesia Stock Exchange from  2014 to 2018. The sampling technique uses a purposive sampling method in which of the 18 companies selected according to the criteria as mush as 11 companies. The analitycal  technique used in this study are multiple linear regression analysis. The result of the analysis showed that the size of  the company and net profit margin does not affect the audit delay while the debt to equity ratio affects the audit delay. the size of the company and the high or low level of profitability does not determine the company will make a delay or delay in the submission of financial statements, as well as companies that have large debts will tend to be faster in delivering financial statement